Diagnostic value of urinary and serum IgG antibodies in evaluating drug treatment response in strongyloidiasis assessed by fecal examination and digital droplet PCR. - Phattharaphon Wongphutorn; Kulthida Y Kopolrat; Chanika Worasith; Chatanun Eamudomkarn; Nuttanan Hongsrichan; Opal Pitaksakulrat; Jiraporn Sithithaworn; Patcharaporn Tippayawat; Anchalee Techasen; Rahmah Noordin; Thomas Crellen; Paiboon Sithithaworn (PLoS ONE)
Detection of Strogyloides-specific IgG antibodies in urine and serum has been used in diagnostic and epidemiological studies on strongyloidiasis. However, the usefulness of these assays in assessing responses to anthelmintic treatment is unclear. Thus, we evaluated the diagnostic performance and temporal profiles of Strongyloides-specific IgG antibodies in a cohort of participants at baseline and post-treatment. The participants were prospectively screened for baseline parasitic infections by fecal examination [agar plate culture technique (APCT) and formalin-ethyl acetate concentration technique (FECT)] and digital droplet polymerase reaction (ddPCR) for Strongyloides stercoralis. At each sampling point, Strongyloides-specific IgG in urine and serum were measured by an in-house S. ratti-based enzyme-linked immunosorbent assay (ELISA). At baseline, 169 of 351 participants (48.1%) had S. stercoralis infection by the combined fecal examination and ddPCR. The diagnostic sensitivities of IgG in urine and serum were 91.1% and 88.2%, respectively. The participants were given treatment with a single oral dose of ivermectin (IVM, 200 μg/kg) and were followed up by fecal and immunological diagnosis at 3 to 18 months post-treatment. The cure rate of IVM treatment evaluated by APCT and ddPCR was 88.3% at three months post-treatment. The profiles of IgG in urine in the curative treatment group showed a significant trend of decline with time post-treatment (Kruskal-Wallis test = 113.4-212.6, p value < 0.0001) and the lowest levels were seen 12 months post-treatment. The treatment response (> 50% reduction in urinary IgG antibody units) was 100%, and conversion from positive to negative results was 65.4%. The treatment response and conversion to negative assessed by serum IgG-ELISA were similar to those by urine IgG-ELISA. The results from this long-term diagnostic study highlight the utility of urinary IgG and serum IgG for screening and monitoring treatment outcomes in strongyloidiasis.